Corporate philanthropy in the United Kingdom - Cowton, Christopher J. (Journal of business ethics, 1987)
The increasing demands placed on private welfare services and calls for business to fulfil its social responsibilities have heightened interest in corporate charitable donations in the United Kingdom. Adjustments to the corporation tax system have been made to encourage companies to give more. The article outlines the legal and fiscal background to company giving, examines its magnitude and reports on a survey of company practice.